Implementation of Flashcards in Increasing Arabic Vocabulary For Junior High School Grade 3 Students for Arabic Speaking Skills - Novel Novel; Nurul Murtadho; Ibnul Samsul Huda (Green Publisher Indonesia, 2025)
This research is motivated by the learning situation in As-Sunnah Junior High School grade 3, which does not use interesting media in learning Arabic, so some students feel bored because of the monotony of learning. The purpose of this research is to design and develop Arabic vocabulary cards taken from the book Durus Al-Lughah Al-Arabiya Lighoiri Natiqin Biha and to find out the opinions of teachers and students about the feasibility of these Arabic vocabulary cards to be used in learning Arabic. The benefit of this research is that students learn vocabulary easily through the media of this vocabulary card for Arabic speaking proficiency. This study uses the R&D method with the ADDIE model (analysis, design, development, implementation, and evaluation). The results of this study obtained an average of 95% validation feasibility from design experts, 68% validation from material experts, 77.9% questionnaire scores obtained from 25 students and 80% of Arabic teachers, and the average result of the percentage of feasibility is 80.23%. So from the average feasibility score of 80.23%, it can be concluded that the Arabic flashcard is based on the book Durus Al-Lughah Al-Arabiya Lighoiri Natiqin Biha volume 2, chapters 16 to 31, which is taken from a conversation lesson written by Dr. Fii. Abdurrahim is interesting or good to be implemented in the 3rd grade of junior high school.